Impaired Processing in the Primary Auditory Cortex of an Animal Model of Autism - Anomal, Renata Figueiredo; de Villers-Sidani, Etienne; Brandão, Juliana Alves; Diniz, Rebecca; Costa, Marcos R.; Romcy-Pereira, Rodrigo N. (Frontiers in Systems Neuroscience, 2015)
Autism is a neurodevelopmental disorder clinically characterized by deficits in communication, lack of social interaction and, repetitive behaviors with restricted interests. A number of studies have reported that sensory perception abnormalities are common in autistic individuals and might contribute to the complex behavioral symptoms of the disorder. In this context, hearing incongruence is particularly prevalent. Considering that some of this abnormal processing might stem from the unbalance of inhibitory and excitatory drives in brain circuitries, we used an animal model of autism induced by valproic acid (VPA) during pregnancy in order to investigate the tonotopic organization of the primary auditory cortex (AI) and its local inhibitory circuitry. Our results show that VPA rats have distorted primary auditory maps with over-representation of high frequencies, broadly tuned receptive fields and higher sound intensity thresholds as compared to controls. However, we did not detect differences in the number of parvalbumin-positive interneurons in AI of VPA and control rats. Altogether our findings show that neurophysiological impairments of hearing perception in this autism model occur independently of alterations in the number of parvalbumin-expressing interneurons. These data support the notion that fine circuit alterations, rather than gross cellular modification, could lead to neurophysiological changes in the autistic brain.